3x-7=x-9
3x-x=-9+7
2x=-2
x=-1
2006-12-04 11:08:34
·
answer #1
·
answered by mr_mumbles_nyc 3
·
0⤊
1⤋
The answers are above in the work of the others. If you wish to check, substitute what you found and check.
3(8) -7 = (8)-9
24 -7 =1
17 doesn't = 1
so you made an error.
to solve:
subtract x from both sides to get
2x - 7 = -9
Then add 7 to both sides
2x = -2
x =-1
Now substitute. and the equation balances.
3(1-) -7 = -1-9
-3 -7 = -10
-10 = -10
2006-12-04 11:15:49
·
answer #2
·
answered by April 6
·
0⤊
0⤋
x = -1
2006-12-04 11:12:00
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
x = -1
2006-12-04 11:11:15
·
answer #4
·
answered by Xiangwei Xi 3
·
0⤊
0⤋
x=1!
2006-12-04 11:11:39
·
answer #5
·
answered by superfly 2
·
0⤊
1⤋
3x-7+x-9. subtract x from both sides (identity), to get
2x-7 = -9. Add 7 to both sides (identity), to get
2x = -2. Now divide both sides by 2, to get
x=-1. To check, 3(-1)-7 = (-1)-9, or
-3-7 = (-10)
-10 = -10 hence, x = -1
2006-12-04 11:12:15
·
answer #6
·
answered by David A 5
·
0⤊
0⤋
8? the answer should be 1 or -1
let me show u :
3x-7=x-9
subtract 7 from both sides
3x=x-2
subtract x from both sides
2x=-2
x=1 or -1
2006-12-04 11:12:11
·
answer #7
·
answered by bigdaddyJJ 1
·
0⤊
1⤋
-1
2006-12-04 11:12:04
·
answer #8
·
answered by Apple 4
·
0⤊
0⤋
3x - 7 = x - 9
2x - 7 = -9 (minus x from both sides)
2x = -2 (add 7 to both sides)
x = -1
2006-12-04 11:10:38
·
answer #9
·
answered by kyls 3
·
0⤊
0⤋
3x - 7 = x - 9
3x - x - 7 = x - x - 9
2x - 7 = -9
2x - 7 + 7 = -9+7
2x = -2
2x / 2 = -2 / 2
x = -1
2006-12-04 11:23:41
·
answer #10
·
answered by mz. * 1
·
0⤊
0⤋
3x - 7 = x - 9
3x - x = -9 + 7
2x = -2
x = -1
2006-12-04 11:10:59
·
answer #11
·
answered by Anonymous
·
0⤊
0⤋